2011
DOI: 10.1111/j.1468-2370.2011.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Management of Innovation: A Systematic Review and Paths for Future Research

Abstract: Strategic management scholars have long emphasized the importance of innovation for a firm's competitive advantage and performance. However, the current state of knowledge about the strategic management of innovation is characterized by conflicting theoretical predictions, persisting knowledge gaps and theoretical inconsistencies. Adopting a ‘systematic’ approach to reviewing the literature, this paper combines different quantitative methods – co‐word analysis, cluster analysis and frequency analysis – to revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
338
0
33

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(375 citation statements)
references
References 216 publications
(405 reference statements)
4
338
0
33
Order By: Relevance
“…Keupp et al [15] made an extensive literature review on innovation management, where when analysing more than 342 papers, they found that there were a low number of papers dealing with the field of non-technical innovation, while the number of papers in the field of product innovation was very high. Camisón and Villar-López [16] also argue that the majority of research on innovation followed a technical focus, concentrating more on product development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keupp et al [15] made an extensive literature review on innovation management, where when analysing more than 342 papers, they found that there were a low number of papers dealing with the field of non-technical innovation, while the number of papers in the field of product innovation was very high. Camisón and Villar-López [16] also argue that the majority of research on innovation followed a technical focus, concentrating more on product development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Envolve ainda tanto a captação de dados objetivos (desempenho financeiro, número de patentes) quanto dados subjetivos, ditas medidas de percepção (percepção quanto aos concorrentes, percepção do desempenho) (Alegre & Chiva 2008;Fosfuri & Tribó, 2009). Keupp, Palmié & Gassmann (2011) realizaram uma revisão sistemática da literatura de 342 artigos sobre a gestão estratégica da inovação e observaram que a maioria dos estudos que analisam os resultados da inovação, a empregam como uma variável dependente, baseada principalmente em patentes, desenvolvimento de novos produtos ou desempenho financeiro. Tradicionalmente o desempenho da inovação em pesquisas de gestão tem sido utilizado como variável dependente, no entanto, pode ser considerado como uma variável intermediária entre certos processos de negócios e o desempenho geral da organização (Alegre, Lapiedra & Chiva, 2006).…”
Section: Desempenho Da Inovação De Produtounclassified
“…São típicas em pesquisas relacionados à estratégia organizacional, quando se apresentam tradicionalmente como variável dependente (Keupp, Palmié & Gassmann, 2011), e, eventualmente, como variável intermediária entre determinados processos de negócios e o desempenho geral da organização (Alegre, Lapiedra & Chiva, 2006).…”
Section: Introductionunclassified
“…Over the past six decades, the literature concerning innovation management has experienced constant evolution (Drejer, 2002;Keupp et al, 2012;Tidd, 2001). Much of the interest centers on the idea that innovation is a driver for competitiveness (see, e.g., Porter, 1990), and some of its positive effects include increases in sales and market share, productivity improvement, and efficiency in operations.…”
Section: Introductionmentioning
confidence: 99%